If it's not what You are looking for type in the equation solver your own equation and let us solve it.
14x+3=9+7x
We move all terms to the left:
14x+3-(9+7x)=0
We add all the numbers together, and all the variables
14x-(7x+9)+3=0
We get rid of parentheses
14x-7x-9+3=0
We add all the numbers together, and all the variables
7x-6=0
We move all terms containing x to the left, all other terms to the right
7x=6
x=6/7
x=6/7
| 45+61=4+2x | | 8c–9=7c | | -32-5x=2x+45 | | 28+39+x=180 | | 3.y=-30 | | 40+15+0.25*m=45+45+0.35*m | | m+5m+-5=7 | | -2(-1+2a)+4(4+2a)=-2 | | (10x+5)+(3x+6)=180 | | 5(u-2)-4=-2(-8u+6)-3u | | y=-30 | | -40+x=23-6x | | 14x+3=9x+7 | | (7x)=(10x-15) | | 7-3(7-2p)=p+21 | | 1.07^x=6,5 | | 1/5x=7–-4/5x | | p/4+10=4 | | 16x=2x+27.4 | | 14p–8=22+20p | | 643=4×164+n | | 30-5p=-3(p-8) | | -20•4x=-0.5x+22 | | 3x+7=2×(x+4)+1 | | 4-6(x-2)=3(x-1)+8 | | -3+3x=4x+8 | | -10–2b=-b | | 20x=20x+17 | | -5=x/13 | | 8k-2(5k-8)=-21 | | 37x+30=9x+42 | | x+4/4=-4 |